Descriptive Epidemiology of Tuberculosis-Diabetes Mellitus Co-Infection in Respira Paru Hospital: A Study of Incidence from 2021 to 2023 - Bunga Bilbina Rizkika; Liena Sofiana; Ardyawati Wira Oktaviana (Knowledge Dynamics, 2025)
Background: Tuberculosis (TB) and Diabetes Mellitus (DM) are global problems, especially in countries with high TB endemicity. The relationship between TB and DM is more dominant in developing countries where TB is endemic, and the prevalence of DM is increasing. The risk of death during TB treatment and the risk of relapse after treatment is higher in TB patients with comorbid DM. More than 10% of TB patients are also known to have DM. This study aims to determine the epidemiological picture of TB-DM incidence based on time, place and person. Methods: This study uses a descriptive quantitative design with a case study approach; the analysis used is univariate analysis using proportions. The population of TB-DM patients in 2021-2023 was recorded in medical records, with a purposive sampling technique obtained from 110 people. Results: The epidemiological picture of TB-DM cases based on the characteristics of the person is age ≥ 45 years (80.9%), male gender (71.8%), type of pulmonary TB (98.2%), bacteriologically confirmed TB diagnosis (73.6%), the final result of TB treatment is cured (52.7%), type of DM therapy is insulin injection (76.4%) and high random blood sugar levels > 200 mg/dL (64.5%). Conclusions: The epidemiological picture of TB-DM cases for three years (2021-2023) has an upward trend and the highest cases in 2022; the majority of TB-DM cases are male, aged > 45 years, with the most cases coming from Bantul Regency.